Reading Galatians 3:28 from a congregational perspective - W.J. Schoeman (Acta Theologica)
How would reading a biblical text (Gal. 3:28) be interpreted from a congregational perspective? First, the article uses a model of African hermeneutics to develop a more contextual reading of a text. Secondly, it discusses the utilisation of congregational hermeneutics in reading a text. This is followed by an empirical reflection to understand the role of reading the biblical text in a congregation. The article identifies themes that may assist in applying the Galatians 3:28 text. African hermeneutics, as a hermeneutical model, assists in having a more contextual reading of a text within an African context. The value of congregational hermeneutics involves the congregation and its members reading the text together. In reading Galatians 3:28 as an “open” text, different congregations may discover the meaning and application of this text for their specific context. It challenges congregations to have a more inclusive identity.